An analysis of generation z prospective mathematics teachers’ understanding of prime numbers in ancient greece - Khairun Nisa; Harisman Yulyanti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
Generation Z prospective mathematics teachers do not have a deep understanding of the history of prime numbers in Ancient Greece. This is an obstacle to their understanding of the application of prime number concepts in learning. This research aims to present the biographies and works of mathematicians of the Ancient Greek era as well as the appreciation of generation Z students of prospective mathematics teachers towards the contribution of mathematicians of the Ancient Greek era in the development of mathematics. The methods used in this qualitative research are literature study and case study. The research subjects consisted of five students of generation Z prospective mathematics teacher who were purposively selected. The data analysis used was thematic analysis. The results showed that most of the subjects had a limited understanding of Ancient Greek mathematicians, but showed interest in learning more about Ancient Greek mathematicians. This study reveals two categories of understanding among the participants: those who unknown about the Ancient Greek mathematicians who contributed to prime numbers and known about the Ancient Greek mathematicians who contributed to prime numbers. Specifically, three participants did not recognize any Ancient Greek mathematicians related to prime numbers, while two participants were able to identify Euclid and Eratosthenes and explain their contributions.